Global impact of anthropogenic NH 3 emissions on upper tropospheric aerosol formation - Christos Xenofontos; Matthias Kohl; Samuel Ruhl; João Almeida; Lucía Caudillo-Plath; Romulo Cruz-Simbron; Lubna Dada; Jonathan Duplissy; Sebastian Ehrhart; Henning Finkenzeller; Kristina Höhler; Weimeng Kong; et al. (Proceedings of the National Academy of Sciences, 2025)
Anthropogenic ammonia (NH 3 ) emissions have significantly increased in recent decades due to enhanced agricultural activities, contributing to global air pollution. While the effects of NH 3 on surface air quality are well documented, its influence on particle dynamics in the upper troposphere-lower stratosphere (UTLS) and related aerosol impacts remain unquantified. NH 3 reaches the UTLS through convective transport and can enhance new particle formation (NPF). This modeling study evaluates the global impact of anthropogenic NH 3 on UTLS particle formation and quantifies its effects on aerosol loading and cloud condensation nuclei (CCN) abundance. We use the EMAC Earth system model, incorporating multicomponent NPF parameterizations from the CERN CLOUD experiment. Our simulations reveal that convective transport increases NH 3 -driven NPF in the UTLS by one to three orders of magnitude compared to a baseline scenario without anthropogenic NH 3 , causing a doubling of aerosol numbers over high-emission regions. These aerosol changes induce a 2.5-fold increase in upper tropospheric CCN concentrations. Anthropogenic NH 3 emissions increase the relative contribution of water-soluble inorganic ions to the UTLS aerosol optical depth (AOD) by 20% and increase total column AOD by up to 80%. In simulations without anthropogenic NH 3 , UTLS aerosol composition is dominated by sulfate and organic species, with a marked reduction in ammonium nitrate and aerosol water content. This results in a decline of aerosol mass concentration by up to 50%. These findings underscore the profound global influence of anthropogenic NH 3 emissions on UTLS particle formation, AOD, and CCN production, with important implications for cloud formation and climate.